1992
DOI: 10.1523/jneurosci.12-01-00319.1992
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between intrinsic firing patterns and thalamocortical synaptic responses of neurons in mouse barrel cortex

Abstract: We used a thalamocortical slice preparation to record both spike trains and synaptically evoked responses from neurons of mouse barrel cortex. Cells were classified as regular spiking (RS), intrinsically bursting (IB), or fast spiking (FS) according to their temporal firing patterns when injected with current. RS cells were further separated into two subtypes, RS1 and RS2 cells, the latter encountered only in the infragranular layers. Synaptic responses were elicited by focal electrical stimuli in the ventroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
230
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(270 citation statements)
references
References 41 publications
(54 reference statements)
33
230
5
Order By: Relevance
“…3C, middle and bottom traces) indicated that it received a thalamocortical input nearly coincident with the monosynaptic field potential. This coincidence, and the negligible sweep-tosweep variability in the onset of the whole-cell responses (note superimposed traces), indicate that these were monosynaptic EPSCs (Agmon and Connors, 1992;Agmon et al, 1996). This neuron discharged a single spike (Fig.…”
Section: Spikes In Inhibitory Interneurons Are Appropriately Timed Tomentioning
confidence: 69%
See 1 more Smart Citation
“…3C, middle and bottom traces) indicated that it received a thalamocortical input nearly coincident with the monosynaptic field potential. This coincidence, and the negligible sweep-tosweep variability in the onset of the whole-cell responses (note superimposed traces), indicate that these were monosynaptic EPSCs (Agmon and Connors, 1992;Agmon et al, 1996). This neuron discharged a single spike (Fig.…”
Section: Spikes In Inhibitory Interneurons Are Appropriately Timed Tomentioning
confidence: 69%
“…Although the thalamocortical input to the neocortex is purely excitatory (glutamatergic), as determined by electrophysiological, electron microscopic, and immunocytochemical evidence (White, 1978;Ferster and Lindstrom, 1983;Agmon and Connors, 1992;Kharazia and Weinberg, 1993), inhibitory (GABAergic) mechanisms are recruited from the very first stage of intracortical processing. Indeed, electrical stimulation of thalamocortical afferents in vivo (Ferster and Lindstrom, 1983;Swadlow, 1989Swadlow, , 1990 or in vitro (Agmon and Connors, 1992;Gil and Amitai, 1996), as well as controlled sensory stimulation (Simons and Carvell, 1989;Simons, 1995;Brumberg et al, 1996;Swadlow et al, 1998;Zhu and Connors, 1999), result in a brief excitation of neocortical neurons, immediately followed by a pronounced inhibitory response mediated by intracortical inhibitory interneurons. The short latency of the inhibitory response indicates that the inhibitory interneurons eliciting it must be excited directly by the thalamocortical afferents, consistent with anatomical data (White, 1978;Fairén and Valverde, 1979;Freund et al, 1985;Keller and White, 1987), and in turn inhibit other cortical neurons disynaptically.…”
mentioning
confidence: 99%
“…These recordings (Fig. 3b) revealed the two known types of layer 5 pyramidal neurons, bursting and regular firing (Agmon and Connors, 1992). Clomeleon-expressing neurons exhibited normal electrophysiological properties when compared to neurons from wildtype mice at P20 (Table 2, ANOVA, p > 0.05), suggesting that they were not compromised by long-term expression of Clomeleon.…”
Section: Long-term Effects Of Clomeleon Expressionmentioning
confidence: 89%
“…Membrane potential recordings were corrected for the liquid junction potential (14 mV). Parameters for wild type tissue were taken from (Pérez-Garci et al, 2006) and (Agmon and Connors, 1992).…”
Section: Targeted Electrophysiological Recordings With Two-photon Lasmentioning
confidence: 99%
“…There are drawbacks to MUA-this measure does not, for example, allow isolation of responses to specific cell types (Agmon and Connors 1992;Bruno and Simons 2002;Andermann et al 2004). That said, our use of MUA in SI facilitated obtaining consistent and high signal-to-noise responses across a large number of conditions (231), and is often employed in auditory studies that apply dense and broad stimulus sampling (Eggermont, 1999;Schreiner and Sutter, 1992).…”
Section: Discussionmentioning
confidence: 99%